Mycobacterial-specific secretion of cytokines and chemokines in healthcare workers with apparent resistance to infection with Mycobacterium tuberculosis - Shey, Muki Shehu; Balfour, Avuyonke; Masina, Nomawethu; Bekiswa, Abulele; Schutz, Charlotte; Goliath, Rene; Dielle, Rachel; Katoto, Patrick DMC.; Wilkinson, Katalin Andrea; Lewinsohn, David; Lewinsohn, Deborah Anne; Meintjes, Graeme (Frontiers in Immunology, 2023)
Background Currently, diagnosis of latent TB infection (LTBI) is based on the secretion of IFN- in response to Mycobacterium tuberculosis (Mtb) antigens, the absence of which is regarded as no infection. Some individuals appear to resist Mtb infection despite sustained exposure (resisters). In this study, we aimed to assess cytokines, chemokines and antibodies that may be associated with resistance to Mtb infection. We hypothesized that there may be an alternative immune response to Mtb exposure in the absence of IFN- in resisters. Methods We enrolled HIV-uninfected healthcare workers who had worked in high TB-exposure environments for 5 years or longer. We screened them for LTBI using the tuberculin skin test and the QuantiFERON TB-PLUS Gold assay. We performed multiplex Luminex to measure concentrations of T cell-associated cytokines and chemokines as well as total antibodies in plasma collected from unstimulated fresh whole blood and supernatants from QuantiFERON TB-PLUS tubes following incubation of whole blood for 20-24 hours with ESAT6/CFP10 peptides. Results Samples from 78 individuals were analysed: 33 resisters (TST<10mm; IGRA<0.35 IU/mL), 33 with LTBI (TST10mm and IGRA0.35 IU/mL) and 12 discordant (TST=0mm; IGRA1.0 IU/mL). There were no differences in concentrations of cytokines and chemokines in plasma between the different groups. Resisters had significantly lower concentrations of IFN-, IL-2, TNF-, MIP-1, MIP-1, ITAC, IL-13 and GM-CSF in supernatants compared with LTBI group. There were no significant differences in the concentrations in supernatants of IL-10, IL-1, IL-17A, IL-21, IL-23, MIP-3, IL-4, IL-5, IL-6, IL-7, IL-8, Fractalkine and IL-12p70 between the groups. We observed that resisters had similar concentrations of total antibodies (IgG1, IgG2, IgG3, IgG4, IgA, and IgM) in plasma and supernatants compared to the LTBI and discordant groups. Conclusion Resistance to Mtb infection despite sustained exposure is associated with lower Mtb-specific secretion of Th1-associated cytokines and chemokines. However, resisters showed secreted concentrations after Mtb stimulation of total antibodies and cytokines/chemokines associated with innate and Th17 immune responses similar to those with Mtb infection. This suggests an ability to mount non-IFN- immune responses to Mtb in apparent resisters.